Strengthening OCB Through Culture and Commitment: A Quantitative Analysis - Sibarani, Albertson; Aryati, Ana Sofia (Jurnal Kewirausahaan dan Inovasi, 2025)
This study aims to examine the influence of organizational culture and organizational commitment on the organizational citizenship behavior (OCB) of employees at PT Bank Rakyat Indonesia Tbk Malang Regional Office. This research is an explanatory research with a quantitative approach, using a saturated sample of 70 employees who have worked for more than one year at PT Bank Rakyat Indonesia Tbk Malang Regional Office. The data analysis technique employed is multiple linear regression using SPSS version 29 as the analytical tool. Data were processed from primary sources obtained through questionnaires using a five-point Likert scale. The results indicate that organizational culture and organizational commitment have a positive correlation and significantly affect the organizational citizenship behavior (OCB) of employees at PT Bank Rakyat Indonesia Tbk Malang Regional Office.